A Pan-Cancer Analysis Reveals the Prognostic and Immunotherapeutic Value of Stanniocalcin-2 (STC2) - Jiang, Zhong-Hui; Shen, Xianfeng; Wei, Yanhong; Chen, Yongji; Chai, Hongbo; Xia, Lingyun; Leng, Weidong (Frontiers in Genetics, 2022)
Abstract Background: Stanniocalcin-2 (STC2) is a secreted glycoprotein and plays an important regulatory role in regulating the homeostasis of calcium, glucose homeostasis, and phosphorus metastasis. Accumulating evidence suggests that STC2 is implicated in cancer mechanisms. However, the effects of STC2 on cancer development and progression across pan-cancer are not yet completely known. Methods: Data were downloaded from The Cancer Genome Atlas database to obtain differentially-expressed genes significantly associated with prognosis (key genes). A gene was selected for subsequent correlation studies by integrating the significance of prognosis and Time-dependent ROC curve. Gene expression of different tumor types was analyzed based on the UCSC XENA website. Further, our study investigated the correlation of STC2 expression between prognosis, immune cell infiltration, immune checkpoints genes (ICGs), mismatch repair genes (MMRs), tumor mutation burden (TMB), microsatellite instability (MSI), and drug sensitive in various malignant tumors. Gene set enrichment analysis (GSEA) was conducted for correlated genes of STC2 to expound potential mechanisms. Results: A total of 3429 differentially-expressed genes and 397 prognosis-related genes were identified from the TCGA database. Twenty-six key genes were found by crossing the former and the latter, and the highest risk gene: STC2 was selected for subsequent correlation studies. STC2 had good diagnostic performance for HNSCC, and was closely related to the survival status and clinicopathological stage of HNSCC patients. In pan-cancer analysis, STC2 was upregulated in 20 cancers and downregulated in 7 cancers. STC2 overexpression was overall negatively correlated with overall survival, disease-free survival, disease-specific survival, and progress-free Survival. STC2 was profoundly correlated with the tumor immune microenvironment, including immune cell infiltration, ICGs, MMRs, TMB, and MSI. Moreover, STC2 was significantly negatively correlated to the sensitivity or resistance of multiple drugs. Conclusion: STC2 was a potential prognostic biomarker for pan-cancer and a new immunotherapy target.